Anterior suspended flaps: a modified approach for external dacryocystorhinostomy. Issue 7 (1st July 1998) - Baldeschi, Lelio; Nardi, Marco; Hintschich, Christoph R; Koornneef, Leo
Abstract : BACKGROUND/AIMS: External dacryocystorhinostomy (DCR) is a reliable but difficult surgical technique for the treatment of any obstruction of the lacrimal drainage system lying distal to the internal opening of the common canaliculus. In this prospective study, a simplified external DCR procedure and the results obtained on a series of 45 consecutive patients, in which traditional external DCR was indicated, are described. METHODS: In this modified procedure only very large and mobile anterior flaps of the lacrimal sac and nasal mucosa are created. Thanks to the large size and the great motility the two flaps can be easily sutured. Two double armed 6/0 polyglycolic acid sutures are used to join the two flaps, to elevate them anteriorly in order to avoid adhesions with underlying tissues, and to approximate the deep planes of the wound. The mean operative time was measured. RESULTS: At the end of follow up period (mean 17 months, range 14–24 months) all patients had no sign or symptoms of tearing and normal Jones I dye test. The mean operative time was 28.6 minutes (range 23–44 minutes) CONCLUSION: We believe that our modified technique can be used to simplify and speed up traditional external DCR without decreasing its well known reliability.